The Livestock Sub-sector in Kenya’s NDC: A scoping of gaps and priorities - Mbae, Robin; Kimoro, Bernard; Kibor, Benjamin T.; Wilkes, Andreas; Odhong’, Charles; Dijk, Suzanne van; Wassie, Shimels Eshete; Khobondo, Joel Onyango (Global Research Alliance on Agricultural Greenhouse Gases (GRA) & CGIAR Research Program on Climate Change Agriculture and Food Security (CCAFS), 2020)
Under the Paris Agreement, countries should update their Nationally Determined Contribution (NDC) every five years, with progressive ambition in each new submission. Kenya plans to review and revise its NDC in June 2020. The State Department for Livestock has undertaken a stock-taking exercise with support from UNIQUE forestry and land use, CCAFS and GRA. This report summarizes the main findings and recommendations for the livestock sub-sector contribution to enhanced climate change ambition. The livestock sub-sector is well aligned with Kenya‘s comprehensive policy framework: The livestock sub-sector is critical to achieving Kenya’s development objectives, including the Big Four Agenda and the Agriculture Sector Growth and Transformation Strategy (ASGTS, 2019-2029). The prioritization exercise that informed the ASGTS highlighted dairy, beef, sheep/goat, poultry and camel as being among Kenya’s 13 value chains with high potential for agricultural transformation and are central to achieving the objectives of the three ASGTS anchors. The Kenya Climate-Smart Agriculture Strategy and Implementation Framework (KCSAIF) sets out clear actions that are in line with livestock sub-sector priorities. With the exception of the dairy industry where some progress has been made, implementation of the KCSAIF in different live-stock industries (e.g., beef, sheep, goats, poultry) is in its early stages. The livestock sub-sector is central to Kenya’s climate change ambitions: Livestock is the largest source of GHG emissions in the agricultural sector, accounting for over 50% of GHG emissions in the Second National Communication, mainly due to enteric fermentation. Trends in livestock GHG emissions are also key drivers of the business as usual (BAU) scenario in Kenya’s first NDC. The projections underlying the BAU scenario in the first NDC assumed 1% annual average growth in enteric fermentation emissions from 2010 to 2030. Official livestock population data combined with IPCC 2006 Tier 1 emission factors show that from 2000 to 2018, enteric fermentation emissions in fact increased by 8.5% per year, and have exceeded the BAU projections in every year since 2007. Assuming annual growth of 3.34%, livestock enteric fermentation emissions in 2030 could exceed 33 Mt CO2e, which is more than double the estimated emissions in 2010. Increasing livestock GHG emissions are mainly driven by rising demand for meat and milk due to increasing population, urbanization and rising incomes. As other sectors decarbonize, agricultural emissions – led by livestock emissions – will become more important. Livestock can also contribute to GHG mitigation. A Dairy NAMA has been proposed, with an estimated mitigation potential of 8.8 Mt CO2e over a 10-year period. The Dairy NAMA has not yet been implemented due to lack of financial support. Other livestock industries also have mitigation potential and there are strong synergies with adaptation. However, the technical feasibility, costs and benefits have not yet been assessed in detail. The majority of non-dairy cattle and small ruminants are raised in the arid and semi-arid areas, where adaptation to climate change and food security are national priorities. Livestock sub-sector contributions to enhanced NDC: NDCs can be enhanced on the basis of a stocking taking of trends, policies and measures, and actions of sub-national and non-state actors in the sector; by updating assumptions and analysis; by ensuring alignment of the NDC with sector development objectives; by ensuring complete coverage of sectors and sub-sectors; and by ensuring that adaptation priorities, policies and plans are appropriately reflected. Based on a stock-taking, the following pathways to NDC enhancement have been identified in the livestock sector. In addition to pursuing financing of the Dairy NAMA, in line with the recommendation in the Mitigation Technical Analysis Report, during the 2018-2022 National Climate Change Action Plan implementation period the livestock sub-sector should build expertise and improve data for mitigation action, while focusing climate change efforts on adaptation. In particular, actions to enhance mitigation ambition and promote adaptation actions are proposed in the following four areas. (1) In-depth assessment and identification of adaptation and mitigation options. This will contribute to identification of feasible livestock sub-sector climate actions for inclusion in the third NDC. •Documentation of vulnerability to climate change and extreme events by livestock in different production systems and in grasslands, for evidenced based development of policies and measures in the livestock sub-sector. •In-depth feasibility assessment in each production system for each livestock species for upscaled implementation of key adaptation and mitigation strategies. •Inventory of domestic (national and county government, non-government, private sector) and internationally-supported initiatives that promote key adaptation and mitigation strategies. •Stakeholder-led identification of adaptation and mitigation initiatives for upscaling. (2) Develop a Livestock Sub-Sector Climate Change Action Plan.T his will support coordination in the sub-sector and assist in resource mobilization for enhanced climate action. •Engage stakeholders and key supporting institutions in the main initiatives in each production system for each species to identify actions to support upscaled implementation of key adaptation and mitigation actions in the livestock sub-sector and ensure coordination with stakeholders. •Develop strategies for the national government to promote climate-smart agriculture (CSA) in the livestock sub-sector, including: -strategies to ensure that these actions are mainstreamed in the workplans of state department for livestock divisions and units and related semi-autonomous government agencies; -strategies to ensure that these actions are mainstreamed in the work of other relevant MDAs and county governments; -strategies to support non-government and private sector actors to address sector support needs; -coordination mechanisms to engage the key stakeholders in each strategy. (3) Improve monitoring and evaluation of livestock sub-sector climate actions. This will support sector coordination, enable tracking of non-state climate actions and support UNFCCC reporting•Design livestock CSA monitoring & evaluation (M&E) system to provide and track information on: -Progress in implementing Livestock Sub-sector Climate Change Action Plan; -KCSAIF M&E framework indicators; -Information required by sub-sector stakeholders; -Other indicators as required by national measurement, reporting and verification (MRV) systems (e.g. adaptation and mitigation action registry). (4) Improve MRV of livestock GHG emissions. This will improve national capacities for MRV to support implementation and tracking of climate actions. •GHG inventory compilation: -Continue to compile and submit the Tier 2 dairy cattle GHG inventory on an annual basis; -Expand application of Tier 2 method to the other livestock species; -Continue to build state department for livestock capacity for GHG inventory compilation. •GHG inventory improvement: -Collaborate with national and county stakeholders to improve livestock administrative statistics in line with GHG inventory data needs; -Strengthen county capacities for improved livestock data collection. •MRV system improvement: -Revise NDC GHG BAU projections for livestock GHG emissions based on Tier 2 emission factors and revised livestock population time series in view of the 2019 livestock census results; -Develop models for tracking change in emission intensity of livestock production in line with key adaptation and mitigation strategies. This report summarizes the state of knowledge and action in the livestock sub-sector regarding adaptation and mitigation, highlighting gaps and priorities for future policy developments. The first chapter provides a general overview of the sector’s position in relation to climate change in Kenya. The following four chapters review priorities for adaptation and mitigation for each of the main livestock species (dairy cattle, non-dairy cattle, small ruminants and poultry). The final chapter assesses policy and institutional issues, and provides recommendations for the State Department for Livestock, with a focus on near-term actions to increase the livestock sector’s support to enhanced climate change ambitions.